Can audience replace execution judges in male gymnastics? - Cuk, I. (Science of Gymnastics Journal, 2015)
The aim of research was to test the qualityof spectators execution evaluation of gymnast`s performance compared to official judges. For the purpose 91 participants (spectators) evaluated 26 exercises on parallel bars on a scale from 0-10.0 points like it is used in diving (0-Completely failed, 0.5-2.0 - unsatisfactory, 2.5-4.5 - deficient, 5.0-6.5 - satisfactory, 7.0-8.0 - good, 8.5-9.5 - very good, and 10 - excellent). Following analysis were performed: Kolmogorov Smirnov test, Cronbach`s Alpha, Spearmans Rank correlation, cluster analyze (square distance method), and Kruskal Wallis analyze of variance. Spectator`s reliability of judging is same as for official judges; ranking is similar to the official judges and even better. Cluster analysis extracted three groups of spectators - strict ones, medium ones and permissive ones. As an average, they function well. The biggest challenge for spectators is bias towards their local (national) heroes and champions. However, in the spectators is also a group of those who are honest and strict without having biased opinion and they formed quite a big group (one quarter).